Nitrite Reductase 1 Is a Target of Nitric Oxide-Mediated Post-Translational Modifications and Controls Nitrogen Flux and Growth in Arabidopsis - Costa-Broseta, Álvaro (Int J Mol Sci, 2020)
Plant growth is the result of the coordinated photosynthesis-mediated assimilation of oxidized forms of C, N and S. Nitrate is the predominant N source in soils and its reductive assimilation requires the successive activities of soluble cytosolic NADH-nitrate reductases (NR) and plastid stroma ferredoxin-nitrite reductases (NiR) allowing the conversion of nitrate to nitrite and then to ammonium. However, nitrite, instead of being reduced to ammonium in plastids, can be reduced to nitric oxide (NO) in mitochondria, through a process that is relevant under hypoxic conditions, or in the cytoplasm, through a side-reaction catalyzed by NRs. We use a loss-of-function approach, based on CRISPR/Cas9-mediated genetic edition, and gain-of-function, using transgenic overexpressing HA-tagged Arabidopsis NiR1 to characterize the role of this enzyme in controlling plant growth, and to propose that the NO-related post-translational modifications, by S-nitrosylation of key C residues, might inactivate NiR1 under stress conditions. NiR1 seems to be a key target in regulating nitrogen assimilation and NO homeostasis, being relevant to the control of both plant growth and performance under stress conditions. Because most higher plants including crops have a single NiR, the modulation of its function might represent a relevant target for agrobiotechnological purposes.